2014
DOI: 10.1111/jerd.12092
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bleaching on Mercury Release from Amalgam Fillings and Antioxidant Enzyme Activities: A Pilot Study

Abstract: Bleaching treatments with the systems tested in this pilot study have no deleterious effect on the mercury release from amalgam fillings and antioxidant enzymes in body fluids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…There are many studies in the literature investigating the effects of Hg on antioxidant activity systems in various tissues and fluids such as saliva and plasma ( 26 , 27 ). While some of these studies found a significant relationship between Hg and antioxidants, some found no significant relationship ( 17 , 26 ). Because Hg can produce reactive oxygen species, it can affect antioxidant enzymes such as SOD-1 and catalase ( 28 ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…There are many studies in the literature investigating the effects of Hg on antioxidant activity systems in various tissues and fluids such as saliva and plasma ( 26 , 27 ). While some of these studies found a significant relationship between Hg and antioxidants, some found no significant relationship ( 17 , 26 ). Because Hg can produce reactive oxygen species, it can affect antioxidant enzymes such as SOD-1 and catalase ( 28 ).…”
Section: Discussionmentioning
confidence: 96%
“…Hg is found in the blood like other body fluids, but its levels in the blood are quite low compared to others. Even in industrial workers exposed to high levels of Hg, measured Hg concentrations have been reported to be in the parts per billion (ppb) range ( 17 ). In the present study, serum Hg concentrations reached the highest level 21 days after treatment (0.91 ng/mL), but no statistically significant difference was found among time periods (p=0.072).…”
Section: Discussionmentioning
confidence: 99%
“…The enzymatic reactions are important for the life of the organisms and enzymes assist life processes in all life forms from viruses to man. These reactions have been naturally designed to function under various physiological conditions [ 1 ], for replacement of old tissues [ 2 ], conversion of food into energy [ 3 ] and disposal of toxic materials [ 4 ].…”
Section: Introductionmentioning
confidence: 99%